Assessing the economic feasibility of high heat treatment, using evidence obtained from pasta factories in Sicily (Italy). (20th January 2017) - Pappalardo, Gioacchino; Chinnici, Gaetano; Pecorino, Biagio
Abstract: Pest control in pasta processing industries is considered to be one of the activities that can have the greatest impact on the environment. However, the adoption of techniques with a lower environmental impact can result in increased production costs that may discourage their adoption by firms, if not adequately compensated by corresponding increase in revenue. The main objective of this study is to evaluate the economic feasibility of High Heat Treatments, a physical method for pest control in industrial plants that produce pasta in Sicily (Italy). A Benefit-Cost Analysis has been conducted in which the costs refer to the implementation of the High Heat Treatments and the benefits were estimated in terms of the potential increase in the pasta factory's turnover. Increases in turnover derive from the impact of a hypothetical eco-friendly mark, based on the consumer's Willingness To Pay for pasta produced by a production process that reduces environmental impact. The results of the Benefit-Cost Analysis have demonstrated that the premium price that consumers recognise for pasta produced with eco-friendly techniques could ensure an increase in turnover of firms making High Heat Treatments economically feasible for the pasta-making industry. Furthermore, this paper could be a guideline for future research towards an integration of non-hypothetical open-ended choice experiment and the economic analysis tool within Benefit-Cost Analysis. Highlights: High Heat Treatments (HHT) are economically feasible inside pasta factories. The consumer's WTP for pasta made with eco-friendly techniques confirms the economic feasibility of HHT. Analysis of consumer's willingness to pay strengthens Benefit-Cost Analysis. Combining Cost-Benefit Analysis and non-hypothetical choice experiments provides useful insights.